SHASHMAQOM MILLIY MUSIQASIMIZ DURDONASI (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This scientific article analyzes the history, developmental stages, andtheoretical foundations of the art of maqom, our national musical heritage, which hasbeen formed over the centuries in Uzbekistan and Central Asia. The inextricableconnection of maqom with music theory, philosophy, and performing traditions isscientifically substantiated. This article focuses on research conducted bymusicologists